Neuroprotective effects of electroacupuncture in ischemic stroke: from mechanisms to clinical implications - Jinxi Zhu; Jinxi Zhu; Jinxi Zhu; Xinyi Ge; Xinyi Ge; Xinyi Ge; Yulong Cao; Yulong Cao; Yulong Cao; Renjie Xiao; Xiao Deng (Frontiers in Aging Neuroscience)
Ischemic stroke is a condition caused by an interruption of blood flow to the brain that can lead to neurological damage. The severe neurological damage caused by an ischemic stroke can lead to cognitive impairment and even disability. Reperfusion therapy is the mainstay of treatment for ischemic stroke. However, while restoring oxygen and blood flow to the brain tissue can reduce or prevent neuronal cell damage and death caused by cerebral ischemia, ischemia/reperfusion may trigger pathological tissue reactions leading to neuronal cell damage. Excessive autophagy in neuronal cells, disruption of cellular oxidative homeostasis leading to oxidative stress, apoptosis, glutamatergic excitatory damage, ferroptosis, and neuroinflammation are all key pathways contributing to cerebral ischemia/reperfusion injury. Electroacupuncture, as an extension of traditional Chinese acupuncture, has obvious effects on alleviating cerebral ischemia/reperfusion injury. Many experiments have observed that after electroacupuncture treatment or pretreatment in rats, cognitive impairment was reduced, brain tissue morphology was improved, and the damage pathways such as autophagy, oxidative stress, neuroinflammation, and apoptosis were significantly inhibited, and the recovery pathways such as the blood-brain barrier and angiogenesis were significantly promoted. Although the specific mechanism of electroacupuncture therapy is not known, it has great potential in the treatment of ischemic stroke and cerebral ischemia/reperfusion injury. Electroacupuncture to improve cerebral ischemia/reperfusion injury is a new target for therapeutic approaches. In the future, electroacupuncture is expected to become an effective therapy for cerebral ischemia/reperfusion by conducting more clinical trials and enriching the understanding of its mechanism for improving cerebral ischemia/reperfusion injury.